Exploring the Creative Geographies of Work with Pre-Service Social Studies Teachers: Exposing intersections of time and labour in New Brunswick, Canada - Burkholder, Casey M.; Chase, Allen (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
What creative approaches might be harnessed to encourage social critique and action in pre-service Geography teacher education? By reflecting on an assignment in Casey’s Introduction to Teaching Geography class where pre-service teachers (including Allen) visually mapped a worker’s labour for a day on unceded and unsurrendered Wolastoqiyik territory (Fredericton, New Brunswick), we ask: What can we learn about work, labour, space, capitalism, and intersectionality by visually mapping a worker’s day and analyzing their labour? We argue that by confronting the apolitical teaching of Geography education through the example of the Mapping Labour assignment, we might attempt to disrupt the ways that European Canadian settler geographies permeate the existing curriculum and work to disrupt neoliberal assumptions about schooling, creativity, and work.